Investigating Leader-Member Exchange (LMX) and Digital Competency's Effects on Organizational Citizenship Behavior (OCB) in Gen Z Retail Employees of Bandung - Imam Heryanto; Windi Matsuko Danasasmita (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2026)
This study aims to examine the extent to which Leader-Member Exchange (LMX) and digital competence influence Organizational Citizenship Behavior (OCB) among Gen Z employees in the retail industry of Bandung. The research employs purposive sampling, selecting respondents who have been employed for at least one year, resulting in a total of 205 participants from the retail sector. Data analysis techniques include quantitative methods to assess the individual and combined effects of LMX and digital competence on OCB. The findings indicate that both LMX and digital skills significantly affect OCB among Gen Z retail employees. The implications of this research provide valuable insights for organizations adapting to digital transformation, emphasizing the importance of effective leadership and the development of relevant digital competencies for the younger workforce.